Environmental Effects of Marine Blasting in Canadian Game Rivers - A Lance McAnuff; Marcus V. van Bers; Andrew Curic (International Society of Explosives Engineers, 1994)
During the summers of 1992 and 1993, blasting operations were carried out to effect the crossing of two of Canada's better known game rivers, the Nipigon and Winnipeg, in connection with the completion of a third natural gas utility across north-western Ontario. The Nipigon River, crossed in 1992, involved a single fast-flowing channel while the Winnipeg River, crossed in 1993, involved three separate channels.